Mesoscale features of monsoon precipitation system as revealed by the objective analysis of rainfall from the use of high dense land rainfall observations - ROY BHOWMIK, S. K.; JOARDAR, D.; ROY, SOMA SEN; HATWAR, H. R. (MAUSAM, 2005)
A simple method for daily rainfall analysis at the resolution of 1° × 1° Lat./Long. over Indian monsoon region is applied from the use of dense land observations and satellite rainfall estimates for the month of June 2001. The results obtained show that the analysis is able to capture large scale as well as mesoscale features of monsoon precipitation system. The availability of this data is expected to be very useful for the synoptic meteorologists and numerical weather prediction modelling community.